2010
DOI: 10.1111/j.1442-200x.2009.02962.x
|View full text |Cite
|
Sign up to set email alerts
|

Survey of severe respiratory syncytial virus infection in Kyoto Prefecture from 2003 to 2007

Abstract: Because severe RSV infection led to sudden death in two cases, detection of RSV is important at admission for an infant with CPAOA. Fourteen patients (66.7%), however, had good outcomes and most patients were extubated within 2 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 11 publications
1
8
1
Order By: Relevance
“…Eight (6.8 %) of our 117 sick RSV-infected patients died. This mortality rate was similar to the published data in the UK (8.6 %) [9] but lower than those in Spain and Japan (over 10 %) [10,11]. Prior sick contact might be a risk factor for RSV-associated mortality among our children who required PICU admission.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Eight (6.8 %) of our 117 sick RSV-infected patients died. This mortality rate was similar to the published data in the UK (8.6 %) [9] but lower than those in Spain and Japan (over 10 %) [10,11]. Prior sick contact might be a risk factor for RSV-associated mortality among our children who required PICU admission.…”
Section: Discussionsupporting
confidence: 88%
“…Bacterial co-infection was present in three of our eight death cases (Table 3). Two recent studies in Asia also reported bacterial co-infections to be associated with severe RSV infections [11,28]. The presence of bacteria in tracheal aspirate might indicate true infection or colonization, but infection biomarkers such as peripheral leucocyte count, lactate dehydrogenase, and C-reactive protein, which were associated with severe RSV infection [16], were not recorded in the case notes from most of our patients.…”
Section: Discussionmentioning
confidence: 65%
“…Furthermore, the absence of obvious clinical signs and symptoms suggests peracute deterioration due to respiratory failure after lower respiratory infection involving diffuse bronchiolitis, resulting in sudden unexpected death in infancy . These findings differed from those of other clinical cases . The prevalence of mortality due to RSV bronchiolitis in infants who are otherwise healthy is <1% .…”
Section: Discussioncontrasting
confidence: 98%
“…We detected bacteria, but considered this as being secondary to RSV infection because blood glucose was not decreased. Pulmonary RSV infection, however, might represent a complication in RSV‐positive viral myocarditis, and mixed infection with RSV might be significant in fatalities due to bacterial pneumonia…”
Section: Discussionmentioning
confidence: 99%
“…The LoS varied according to patient age [76,77], severity of infection [78,79], body weight [52], presence or absence of wheezing at the time of admission [25], presence or absence of hypoxia [58], season [80], and RSV subgroups [81] (Fig. 4).…”
Section: Hospitalization and Losmentioning
confidence: 99%